Numerical study of blast-resistant sandwich panels with rotational friction dampers - Chen, Wensu; Hao, Hong (World Scientific Publishing Co. Pte. Ltd., 2013)
Blast-resistant structures are traditionally designed with solid materials of huge weight to resist blast loads. This not only increases the construction costs, but also undermines the operational performance. To overcome these problems, many researchers develop new designs with either new materials or new structural forms, or both to resist the blast loads. Friction damper, as a passive energy absorber, has been used in earthquake-resistant design to absorb vibration energy from cyclic loading. The use of friction damper in blast-resistant design to absorb high-rate impact and blast energy, however, has not been well explored. This study introduces a new sandwich panel equipped with rotational friction hinge device with spring (RFHDS) between the outer and inner plates to resist the blast loading. This device RFHDS, as a special sandwich core and energy absorber, consists of rotational friction hinge device (RFHD) and spring. The RFHD is used to absorb blast energy while the spring is used to restore the original shape of the panel. This paper studies the mechanism of RFHD by using theoretical derivation and numerical simulations to derive its equivalent force-displacement relation and study its energy absorption capacity. In addition, the energy absorption and blast loading resistance capacities of the sandwich panel equipped with RFHDS are numerically investigated by using Ls-Dyna. It is found that the proposed sandwich panel can recover, at least partially its original configuration after the loading and thus maintain its operational and blast-resistance capability after a blasting event. In order to maximize the performance of the proposed sandwich panel, parametric calculations are carried out to study the performance of RFHDS and the sandwich panels with RFHDS. The best performing sandwich panel with RFHDS in resisting blast loadings is identified. This sandwich panel configuration might be employed to mitigate blast loading effects in structural sandwich panel design.